DANISH SUPPORT FOR THE BALTIC STRUGGLE FOR INDEPENDENCE 1988-1991: A HAWK-DOVE DOMESTIC CONFRONTATION - Olesen, Mikkel Runge (Baltic Journal of Political Science, 2015)
When the Baltic States regained their independence in 1991, Denmark had been one of their very strongest supporters, at a time when many European countries looked at the Baltic aspirations with caution. It was one of the first examples of the new post-Cold War “activist” Danish foreign policy strategy. It was not, however, without difficulties. Thus, the article argues that the Danish Social Democratic centre-left and Conservative-Liberal centre-right disagreed on how to support the Balts in practice and at what price. The difference was rooted in a hawk-dove disagreement over détente and the Soviet Union. Government party colour, the article argues, is therefore likely to have been crucial for the Danish policy. Had the relatively hawkish centre-right government not been in power, it is very doubtful that we would have seen the kind of aggressive diplomatic support for Baltic independence as we saw from Denmark leading up to 1991.